Methylene-Blue-Encapsulated Liposomes as Photodynamic Therapy Nano Agents for Breast Cancer Cells - Wu, Po-Ting (Nanomaterials (Basel), 2018)
Methylene blue (MB) is a widely used dye and photodynamic therapy (PDT) agent that can produce reactive oxygen species (ROS) after light exposure, triggering apoptosis. However, it is hard for the dye to penetrate through the cell membrane, leading to poor cellular uptake; thus, drug carriers, which could enhance the cellular uptake, are a suitable solution. In addition, the defective vessels resulting from fast vessel outgrowth leads to an enhanced permeability and retention (EPR) effect, which gives nanoscale drug carriers a promising potential. In this study, we applied poly(12-(methacryloyloxy)dodecyl phosphorylcholine), a zwitterionic polymer-lipid, to self-assemble into liposomes and encapsulate MB (MB-liposome). Its properties of high stability and fast intracellular uptake were confirmed, and the higher in vitro ROS generation ability of MB-liposomes than that of free MB was also verified. For in vivo tests, we examined the toxicity in mice via tail vein injection. With the features found, MB-liposome has the potential of being an effective PDT nano agent for cancer therapy.